Cyclooxygenase-2 Level in Bilharzial and Non-Bilharzial Related Bladder Cancer among Iraqi Patients - Sinan Qayes Khayoon; Ghada B. Al-Omashi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Bladder cancer has become common cancer globally. It is the most common urological cancer; it comprises asignificant part of urologists’ work. 80 % of bladder cancers are superficial at diagnosis; they have not invadedinto the muscle. The residual 20% are muscle-invasive, which carry a much worse prognosis. Emergingevidence mark that some parasites such as the blood fluke Schistosoma haematobium, Clonorchis Sinensisand small liver flukes Opisthorchis viverrini are causative agents of malignancies such as bladder cancercaused by schistosomes and cholangiocarcinoma by liver flukes. Infection with Schistosoma haematobiumleads to urogenital schistosomiasis, which has been correlated with the occurrence of bladder cancer. Themechanisms responsible for this association have not yet been clearly identified. This study clarifies theassociation between cyclooxygenase-2 (COX2) and bladder lesions associated with Schistosoma. The resultshows there is a high expression of COX2 in the Bilharzia related bladder cancer (BBC) while there is lowexpression of COX2 in non-bilharzia related bladder cancer (NBBC). In conclusion, conceder the positiveexpression of COX2 among Iraqi patients with Schistosomal-related bladder lesions is high. There may bea strong association between high rates of bladder cancer and urinary schistosomiasis in Iraq, as the vastmajority of COX2 lesions were positive.